DESIGN DEVELOPMENT OF AUDIOVISUAL TEACHING MATERIALS FOR CANVA APPLICATION-BASED READING SKILLS IN EARLY CHILDHOOD - Usmiyatun, Usmiyatun; Arian Sah, Retno Wahyu; Santiago, Paulo Victor da Silva (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2023)
Mathematics learning is not optimal because of limited learning media. Most teachers rely solely on manual materials and exercises, which are too limiting. This study aims to create audiovisual learning media based on the Canva application for reading skills in in early childhood (PAUD). This type of research is media development based on the four-D development model. Due to the limitations of researchers, the development of this media has only reached the development stage. In other words, it has just reached the validation stage by the validator. The subjects of this research were two media professionals, two materials professionals, and two practitioners, as well as fifteen students. Data collection methods in this study are observation, interview, and questionnaire methods. The data were analyzed qualitatively and quantitatively using the average formula to obtain an average efficacy score. The results showed that audiovisual media based on the Canva application-based reading skills in early childhood (PAUD) obtained a relevance score of 4.73 for material experts and 4.92 for media experts. Based on audiovisual media from the Canva application-assisted learning development.